A Preliminary Estimation of Carbon Stock Sequestrated through Rubber (Hevea brasiliensis) Plantation in North Eastern Region of India - Dey, S. K. (Indian Forester, 2005)
Global concern on increasing levels of greenhouse gases specifically carbon dioxide in the atmosphere, has led to the search for various mitigation options. In this context, carbon sequestration through managed rubber plantation is gaining importance. Rubber plantation has been expanding in the North East (NE) region and covers an area of 51,510 hectare. In this study, the carbon stock of rubber plantation in the NE region has been estimated and results indicate that an average carbon store in rubber plantation is around 136 tonnes/ha, out of which 92.7 t C/ha is contributed by soil and 2.40 t C/ha addition through litter fall and undergrowth vegetation. About seven million tonnes of carbon is store in the rubber plantations of this region. On completion of projected area of 4,50,000 ha., the carbon store would be around nine times higher than the present value. This study reflects the immense ecological value that rubber plantations provide, by storing carbon despite low productivity in these marginal lands.